"ME TOO" AT THE MOVIES: THE WIFE AND COLETTE. Issue 3 (3rd July 2019) - Steinberg, Marcia; Weisel-Barth, Joye
Abstract : The Wife and Colette are a pair of films reflective of the "Me Too" era. The movies, released in 2018 within a month of each other, share the familiar theme of the enslaved wife and the smarmy, entitled husband, a man who neither measures up to nor deserves to kiss the woman's toes. Coincidently, in both films the wives start out as loving, submissive girls and gifted writers who adore their husbands and allow the men to take credit for their wildly successful literary work. Marcia Steinberg reviews The Wife, and I examine Colette. — Joye Weisel-Barth